Decidual mesenchymal stem/stromal cells from preeclamptic patients secrete endoglin, which at high levels inhibits endothelial cell attachment invitro. (August 2022) - Perera, C.; Zheng, S.; Kokkinos, M.I.; Georgiou, H.M.; Schoppet, M.; James, P.F.; Brennecke, S.P.; Kalionis, B.
Abstract: Introduction: In preeclampsia (PE), inadequate remodelling of spiral arterioles in the decidua basalis causes oxidative stress and subsequent increased release of antiangiogenic soluble endoglin (sENG) into the maternal circulation. Decidual mesenchymal stem/stromal cells (DMSCs) reside adjacent to endothelial cells in this vascular niche. Surprisingly, DMSCs express membrane-bound ENG (CD105). PE-affected DMSCs (PE-DMSCs) are abnormal and due to reduced extravillous invasion, more of them are present, but the significance of this is not known. Methods: DMSCs were isolated and characterised from normotensive control and severe-PE placentae. Extracellular vesicle (EV) types, shed microvesicles (sMV) and exosomes, were isolated from DMSC conditioned media (DMSCCM ), respectively. Secretion of ENG by DMSCs was assessed by ELISA of DMSCCM, with and without EV depletion. The effects of reducing ENG concentration, by blocking antibody, on human umbilical vein endothelial cell (HUVEC) attachment were assessed by xCELLigence real-time functional assays. Results: ENG was detected in DMSCCM and these levels significantly decreased when depleted of exosomes and sMV. There was no significant difference in the amount of ENG secreted by control DMSCs and PE-DMSCs. Blocking ENG in concentrated DMSCCM, used to treat HUVECs, improved endothelial cell attachment. Discussion: In normotensive pregnancies, DMSC secretion of ENG likely has a beneficial effect on endothelial cells. However, in PE pregnancies, shallow invasion of the spiral arterioles exposes more PE-DMSC derived sources of ENG (soluble and EV). The presence of these PE-DMSCs in the vascular niche contributes to endothelial cell dysfunction. Highlights: DMSCs secrete ENG in a soluble form, but ENG is also in extracellular vesicles. Normotensive DMSCs and PE-DMSCs secrete similar quantities of ENG. ENG affects HUVEC function in a dose-dependent manner. Lower than threshold levels of DMSC-secreted ENG promote HUVEC attachment. Higher than threshold levels of DMSC-secreted ENG suppress HUVEC attachment.